IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SMP AL ISMAILIYAH BERINGIN, TAMBELANGAN, SAMPANG - Mobazzir Mobazzir; Moh. Ari Wibowo; Risqi Hartiasih Soetomo (Jurnal Cendekia Pendidikan, 2025)
The paradigm shift in national education through the implementation of the Merdeka Curriculum has elicited various responses among educators, particularly in the subject of Pancasila Education. This issue has become controversial because not all teachers are adequately prepared and understand the principles of competency- and character-oriented learning. This study aims to analyze teachers' understanding of the implementation of the Merdeka Curriculum in Pancasila Education at Al Ismailiyah Beringin Junior High School, Tambelangan, Sampang, in the 2023–2024 academic year. This study uses a qualitative approach with field research. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using Miles and Huberman's interactive model, which includes data reduction, data presentation, and conclusion drawing. The results show that teachers have a good understanding of the principles of the Merdeka Curriculum, including differentiated learning, diagnostic assessment, and the integration of Pancasila values. The implementation of this curriculum contributes to an increase in students' nationalism, responsibility, and social skills. However, challenges were found in the form of limited resources and pedagogical adaptation at the school level. These findings emphasize the urgency of implementing the Merdeka Curriculum (change and solution) as an effort to restore post-pandemic learning and strengthen the Pancasila Student Profile in the context of 21st-century education.